Alternatively Activated (M2) Macrophage Phenotype Is Inducible by Endothelin-1 in Cultured Human Macrophages - Soldano, Stefano; Pizzorni, Carmen; Paolino, Sabrina; Trombetta, Amelia Chiara; Montagna, Paola; Brizzolara, Renata; Ruaro, Barbara; Sulli, Alberto; Cutolo, Maurizio (PloS one, 2016)
Alternatively activated (M2) macrophages are phenotypically characterized by the expression of specific markers, mainly macrophage scavenger receptors (CD204 and CD163) and mannose receptor-1 (CD206), and participate in the fibrotic process by over-producing pro-fibrotic molecules, such as transforming growth factor-beta1 (TGFbeta1) and metalloproteinase (MMP)-9. Endothelin-1 (ET-1) is implicated in the fibrotic process, exerting its pro-fibrotic effects through the interaction with its receptors (ETA and ETB). The study investigated the possible role of ET-1 in inducing the transition from cultured human macrophages into M2 cells. Cultured human monocytes (THP-1 cell line) were activated into macrophages (M0 macrophages) with phorbol myristate acetate and subsequently maintained in growth medium (M0-controls) or treated with either ET-1 (100nM) or interleukin-4 (IL-4, 10ng/mL, M2 inducer) for 72 hours. Similarly, primary cultures of human peripheral blood monocyte (PBM)-derived macrophages obtained from healthy subjects, were maintained in growth medium (untreated cells) or treated with ET-1 or IL-4 for 6 days. Both M0 and PBM-derived macrophages were pre-treated with ET receptor antagonist (ETA/BRA, bosentan 10-5M) for 1 hour before ET-1 stimulation. Protein and gene expression of CD204, CD206, CD163, TGFbeta1 were analysed by immunocytochemistry, Western blotting and quantitative real time polymerase chain reaction (qRT-PCR). Gene expression of interleukin(IL)-10 and macrophage derived chemokine (CCL-22) was evaluated by qRT-PCR. MMP-9 production was investigated by gel zymography. ET-1 significantly increased the expression of M2 phenotype markers CD204, CD206, CD163, IL-10 and CCL-22, and the production of MMP-9 in both cultures of M0 and PBM-derived macrophages compared to M0-controls and untreated cells. In cultured PBM-derived macrophages, ET-1 increased TGFbeta1 protein and gene expression compared to untreated cells. The ET-1-mediated effects were contrasted by ETA/BRA treatment in both cultured cell types. ET-1 seems to induce the M2 phenotype in cultured human macrophages, a process apparently contrasted by the action of the ETA/BRA, suggesting possible clinical implications in those fibrotic diseases characterized by increased ET-1 concentrations, such as systemic sclerosis but also type 2 diabetes.